Identification of Protective Antigens for Vaccination against Systemic Salmonellosis - Bumann, Dirk (Frontiers in Immunology, 2014)
There is an urgent medical need for improved vaccines with broad serovar coverage and high efficacy against systemic salmonellosis. Subunit vaccines offer excellent safety profiles but require identification of protective antigens, which remains a challenging task. Here, I review crucial properties of Salmonella antigens that might help to narrow down the number of potential candidates from more than 4000 proteins encoded in Salmonella genomes, to a more manageable number of 50–200 most promising antigens. I also discuss complementary approaches for antigen identification and potential limitations of current pre-clinical vaccine testing.